Studies in South African infant growth, illustrated by comparative analyses of groups of European, Coloured, Bantu and Indian babies from birth to one year - Salber, Eva Juliet (Department of Medicine, 2020)
There are four main ethnic groups in South Africa- European, Coloured, Bantu and Indian. Each differs widely from the other in socio-economic status and cultural background. This being so it seems to me that in South Africa one has a unique opportunity for doing comparative research. For many years i have been interested in health rather than in disease, and growth in infancy is, I think, a good index of health. I believe that an examination of the growth pattern of infants from birth to one year gives one a good idea of the health and standard of living of a population in general and of its infants in particular.